2019
DOI: 10.34084/bshr.576663
|View full text |Cite
|
Sign up to set email alerts
|

Tıbbi Sülük Terapisi (Hirudoterapi)

Abstract: Sülükler halkalı omurgasızlar sınıfındadır, kan ile beslenirler ve antik dönemden beri çeşitli hastalıkları tedavi etmek için flebotomide kullanılırlar. Hirudoterapi, tedavi için tıbbi sülüklerin uygulanmasıdır. Sülük tedavisinin terapötik kullanımı köklü bir yöntemdir ve eski Mısır'a, medeniyetin başlangıcına dayanır. 20. yüzyılın sonunda yeni terapi kavramları sülük tedavisinin yerini almıştır. Mikrovasküler cerrahi tekniklerle birlikte son yıllarda tıbbi sülüklerin kullanımında bir "yeniden doğuş" olmuştur.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
5
0
3
Order By: Relevance
“…It is believed that leeches can cause trauma to the vaginal mucosa, which can lead to bleeding. Due to the anticoagulant component of leech saliva, a leech bite may cause prolonged bleeding that cannot be stopped with compression (8,9,10). The risk of mortality increases in patients with a history of anticoagulant, antiplatelet, and non-steroidal anti-inflammatory drug (NSAID) use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that leeches can cause trauma to the vaginal mucosa, which can lead to bleeding. Due to the anticoagulant component of leech saliva, a leech bite may cause prolonged bleeding that cannot be stopped with compression (8,9,10). The risk of mortality increases in patients with a history of anticoagulant, antiplatelet, and non-steroidal anti-inflammatory drug (NSAID) use.…”
Section: Discussionmentioning
confidence: 99%
“…However, normal prothrombin and activated partial thromboplastin times may not exclude severe coagulation disorders. Hirudin and other bioactive substances secreted by leeches can impair coagulation without affecting the results of coagulation tests (1,9). The management of vaginal bleeding after intravaginal leech administration depends on the severity of the bleeding.…”
Section: Histamine-like Substancesmentioning
confidence: 99%
“…After attaching to mucosal membrane, they secrete saliva containing anticoagulant, hirudin, and histamine-like substances, which can cause continuing mucosal bleeding ( 6 ). The clinical signs of bleeding can be epistaxis, hemoptysis, or even anemia ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leech muscle structure is composed of muscle fibers which are arranged from outside to inside; consisting circular, diagonal and longitudinal fibers. In addition, there are dorso-ventral located muscle fibers ( 7 ). In previous studies, acetylcholine was shown in the leech nervous system, and it has been isolated after stimulation of the nerves leading to the dorsal muscles of the leech.…”
Section: Discussionmentioning
confidence: 99%
“…Latincede "Hirudotherapy" olarak bilenen kavram, hastalıkların tıbbi sülükler ile tedavisinin yapılması olarak tanımlanmaktadır (41). Bu uygulamanın yaklaşık 2500 yıl öncesinde Antik Mısır'da kan almak için kullanıldığını bilinmektedir.…”
Section: Sülük Uygulamasıunclassified